TEMPERATURE DEFORMATIONS OF FIBROCONCRETE - Gulomiddinov Sarvar Gayratjonovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The types of temperature deformations of concrete are studied and analyzed in the article. According to the results of the analysis, the penetration deformations increase in the hot season, and in the cold and high humidity periods, the growth decreases and gradually turns into the expansion deformation. The influence of the dimensions of the concrete section on the initial deformation plays a major role in the initial periods of construction operation.